1998
DOI: 10.1097/00005537-199805000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Electrical Stimulation on Spiral Ganglion Neuron Survival and Size in Deafened Kittens

Abstract: We have studied spiral ganglion cell (SGC) survival and soma size in neonatally pharmacologically deafened kittens. They were implanted with a four-electrode array in the left cochlea at 100 to 180 or more days of age. Eight animals were chronically stimulated approximately 1000 hours over approximately 60 days with charge-balanced, biphasic current pulses; three were unstimulated controls. Using three-dimensional computer-aided reconstruction of the cochlea, the SGC position and cross-sectional area were stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 19 publications
9
54
1
Order By: Relevance
“…There was no significant effect of chronic ES alone on SGN survival, a finding consistent with previous studies in the cat [27,31,32] and guinea pig [8,33,34], although this is not a uniform finding [25,[35][36][37][38][39][40][41]. Differences in the methodology (e.g., the duration and severity of deafness, the age at deafness onset, electrode design and position, duration, and mode of chronic ES) complicate direct The mean (± SEM) of peripheral process packing density expressed as a percentage of the OSL.…”
Section: Effects Of Chronic Es On Sgn Survivalsupporting
confidence: 91%
“…There was no significant effect of chronic ES alone on SGN survival, a finding consistent with previous studies in the cat [27,31,32] and guinea pig [8,33,34], although this is not a uniform finding [25,[35][36][37][38][39][40][41]. Differences in the methodology (e.g., the duration and severity of deafness, the age at deafness onset, electrode design and position, duration, and mode of chronic ES) complicate direct The mean (± SEM) of peripheral process packing density expressed as a percentage of the OSL.…”
Section: Effects Of Chronic Es On Sgn Survivalsupporting
confidence: 91%
“…Profound deafness has been reported to result in reduction in the size of SG neuron perikarya in many previous studies and in various deaf animal models (Agterberg et al 2008(Agterberg et al , 2009Araki et al 1998;Elverland and Mair 1980;Glueckert et al 2008;Leake et al 1999Leake et al , 2007Leake et al , 2011; Leake and Hradek 1988;McGuinness and Shepherd 2005;Shepherd et al 2005;Wise et al 2005). Presumably, reduction in somatic size reflects reduced metabolic requirements of these neurons due to reduced spike activity after deafness (Hartmann et al 1984;Liberman and Kiang 1978;Shepherd and Javel 1997).…”
Section: Effects Of Deafness Bdnf and Es On Sg Cell Soma Sizementioning
confidence: 95%
“…Presumably, reduction in somatic size reflects reduced metabolic requirements of these neurons due to reduced spike activity after deafness (Hartmann et al 1984;Liberman and Kiang 1978;Shepherd and Javel 1997). When electrical stimulation from a CI is applied to reactivate these neurons, modest but significant increases in SG soma area in the stimulated cochleae have been reported (Araki et al 1998;Coco et al 2007;Leake et al 1999Leake et al , 2007. However, the effects on soma area associated with neurotrophin administration are much greater than the cell size changes elicited with electrical stimulation.…”
Section: Effects Of Deafness Bdnf and Es On Sg Cell Soma Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Lousteau (1987), Hartshorn et al (1991), and Miller and Altschuler et al (1995; demonstrated increased SG cell survival after chronic ICES in guinea pigs deafened by ototoxic drugs and implanted as young adults. In contrast, other studies have failed to find trophic effects in vivo in guinea pigs , and Shepherd and coworkers (Araki et al, 1998;Shepherd et al, 1994) found no overall difference in SG cell survival after chronic ICES in cats deafened at an early age by ototoxic drugs, although recently they reported a significant regional increase in SG survival in partially deafened cats and a consistent increase in the size of stimulated SG cells (Coco et al, 2007).…”
Section: Factors Influencing Neurotrophic Effects Of Electrical Stimumentioning
confidence: 96%